Modern Wound Care Using Cadexomer Iodine 0,9% Dressing in the Granulation Process of a Grade 4 Diabetic Foot Ulcer: Case Study - Della Safitri; Andi Mappanganro; Haeril Amir; Wa Ode Sri Asnaniar (An Idea Nursing Journal, 2025)
Diabetic foot ulcers are a serious complication of diabetes mellitus that require comprehensive management to prevent further adverse outcomes. This study aimed to evaluate the effect of modern wound management using 0.9% cadexomer iodine on the granulation process in a grade 4 diabetic foot ulcer. A case study was conducted involving a 54-year-old male patient, referred to as Mr. “Z,” who received 0.9% cadexomer iodine as part of his wound care intervention three times per week. The findings demonstrated an increase in granulation tissue of up to 75% as measured by the Bates-Jensen Wound Assessment Tool (BWAT) during the treatment period. The use of 0.9% cadexomer iodine was found to be effective in enhancing granulation tissue formation and promoting wound healing in diabetic foot ulcers.